2002
DOI: 10.3322/canjclin.52.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Cancer Communication

Abstract: Health literacy is increasingly recognized as a critical factor affecting communication across the continuum of cancer care. We reviewed research on health literacy and examined its impact on cancer outcomes and communication. According to the National Adult Literacy Survey (NALS), considered the most accurate portrait of literacy in our society, about one in five American adults may lack the necessary literacy skills to function adequately in our society. As patients, such individuals are at a disadvantage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
492
1
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(525 citation statements)
references
References 69 publications
10
492
1
11
Order By: Relevance
“…56,59 Latina women exhibited low literacy levels such as difficulty understanding written medical communication. Low literacy poses a concern as studies have reported delays in diagnosis 60 and lack of knowledge of the benefits of early cancer detection 61 with low health literacy. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…56,59 Latina women exhibited low literacy levels such as difficulty understanding written medical communication. Low literacy poses a concern as studies have reported delays in diagnosis 60 and lack of knowledge of the benefits of early cancer detection 61 with low health literacy. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Cenesiz and Atak indicated that a positive relation was found between the level of knowledge of breast cancer with BSE and mammography. Some studies have reported that knowledge influence cancer screening practices (Davis et al, 2002;Chiu et al, 2005;Elmubarak et al, 2005;Markovic et al, 2005;Kwon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To have a fatalistic view can be a barrier for the people to take an effective role in health behaviors. Some studies indicate among some population subgroups, fatalism has been described as the belief that cancer "is unpreventable, untreatable, inevitable and ultimately leads to death" (Davis et al, 2002;Young et al, 2002;Elmubarak et al, 2005). Not go to the doctors for control unless people do not feel fine, negatively affect the early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This included an hour-long training and education session that reviewed the current American Cancer Society screening recommendations and the use of specific communication skills identified in health literacy initiatives (e.g., avoidance of medical jargon, teach back, layering of health information). 16 Colonoscopy was viewed as the preferred recommendation. However, FOBT and flexible sigmoidoscopy were also available and considered equally viable screening tests for patients.…”
Section: Overviewmentioning
confidence: 99%